Pemodelan Dan Simulasi Motor Kapasitor Pada Kondisi Variable Speed - Adisa Adisa; Budhi Anto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Permanent Split Capacitor (PSC) Motor is a type of single-phase induction motor which widely used and one of circuit to run the water pump. The water pump is needed in the irrigation of agricultural land. If the location of agricultural land is not supplied with electricity grid, then the Water Pump may be driven by solar modules. This paper describes a design of power electronics system that convert DC Power from Solar Panels into AC Power for supplying the PSC Motor. The idea of this paper is to look at the speed characteristics of PSC Motor from the effect of sunlight Irradiance. The system is simulated using MATLAB-Simulink R2015a. The system driver consist of Push Pull Converter and Full Bridge Inverter type. DC voltage of the solar panel is raised to 311 V using Push Pull Converter, then the voltage is converted into AC voltage using the full bridge inverter. PSC Motor models and solar module models are using the available models in the MATLAB-Simulink R2015a library. The Motor Capacitor models is using the Single Phase Asynchronous Machine models and Capacitor of 16 μF. The Motor parameters is using the parameters that have been proposed by Hrabovcova V. The solar Modules use the MEMC Singapore MEMC-M250ACA-20. In this research, the solar panel was given the sunlight Irradiance with 5 conditions, the condition is: Irradiance 1000 W/m2, 800 W/m2, 600 W/m2, 400 W/m2, and 200 W/m2. The effect of sunlight Irradiances shows the speed characteristics of PSC motor that follows logarithmic trendline.Keywords: Solar Module, Push-Pull Converter, Full Bridge Inverter, Permanent Split Capacitor Motor, MATLAB-Simulink.